Radiation effect on mhd stagnation-point flow of a nanofluid over a nonlinear stretching sheet with convective boundary condition - Imran, Anwar; Sharidan, Shafie; Abdul Rahman, Kasim; Mohd Zuki, Salleh (Begell House, 2016)
The effect of radiation on the MHD stagnation-point fl ow of a nanofluid over a nonlinear stretching sheet with convective boundary condition is investigated numerically. A small magnetic Reynolds number and Rossel and approximation are also assumed in this study where the sheet is stretched with a power law velocity in the presence of a nonuniform magnetic field applied in the y direction normal to the fl ow on the sheet. A highly nonlinear problem is modeled using the modified Bernoulli equation for an electrically conducting nano fluid. The momentum, thermal, and concentration boundary-layer thicknesses are intensified with increasing values of the velocity ratio parameter. By using appropriate similarity transformation, the system of nonlinear partial differential equations is reduced to ordinary differential equations. These equations subjected to the boundary conditions are solved numerically using the Keller-box method. Numerical results are plotted and discussed for pertinent flow parameters. A comparison with previous results given in the literature is also made.